Inovasi Layanan Seluler Peternakan Terintegrasi (La Sapi) Kabupaten Sinjai - Riskasari Riskasari (Kolaborasi : Jurnal Administrasi Publik, 2021)
Public demands for improving good and satisfying public services are one of the needs that must be met by the government. This study aims to determine the innovation of integrated livestock cellular service (LA SAPI) in Sinjai Regency. This research is a qualitative research, the research conducted is descriptive, so it requires observation, interviews and documentation as data collection techniques. Based on the findings that the integrated livestock cellular service innovation (LA SAPI) on the relative advantage attribute, it is known that the advantage of the integrated livestock cellular service innovation is to minimize brokering practices and make it easier for the public The compatibility attribute explains that the innovation of integrated livestock cellular services is in accordance with the wishes of the community in making buying and selling transactions easier. The complexity attribute explains that there is no complexity in using the integrated farm mobile service even easier. The triability attribute also explains that there is no trial phase for the community in the service. There was only a technical experiment at the Sinjai District Animal Husbandry Office. The observability attribute shows that as long as the integrated livestock cellular service is in accordance with the wishes of the Livestock Service Office of Sinjai Regency because it can realize the performance of public services and to facilitate the community in the buying and selling process and increase the income of farmers in minimizing brokering. Tuntutan masyarakat terhadap peningkatan pelayanan publik yang baik dan memuaskan menjadi salah satu kebutuhan yang harus dipenuhi oleh pemerintah. Penelitian ini bertujuan untuk mengetahui inovasi layanan seluler peternakan terintegrasi ( LA SAPI) Kabupaten Sinjai. Penelitian ini merupakan penelitian kualitatif, dalam penelitian yang dilakukan bersifat deskriptif, sehingga diperlukan observasi, wawancara maupun dokumentasi sebagai teknik pengumpulan data. Berdasarkan temuan bahwa inovasi layanan seluler peternakan terintegrasi ( LA SAPI) pada atribut relative advantage diketahui bahwa keuntungan dari adanya inovasi layanan seluler peternakan terintegrasi adalah meminimalisir praktek percaloan dan lebih memudahkan masyarakat. Pada atribut compatibility menjelaskan bahwa inovasi layanan seluler peternakan terintegrasi sesuai dengan keinginan masyarakat dalam proses transaksi jual beli lebih mudah. Atribut complexity menjelaskan bahwa tidak ada kerumitan dalam penggunakan layanan seluler peternakan terintegrasi bahkan lebih memudahkan. Atribut triability juga menjelaskan bahwa tidak adanya fase uji coba kepada masyarakat dalam layanan. Hanya ada percobaan teknis di Kantor Dinas Peternakan Kabupaten Sinjai. Pada atribut observability menunjukkan bahwa selama layanan seluler peternakan terintegrasi telah sesuai dengan keinginan Dinas Peternakan Kabupaten Sinjai karena dapat mewujudkan kinerja pelayanan public serta untuk memudahkan masyarakat dalam proses jual beli dan meningkatkan pendapatan peternak dalam meminimalisir percaloan.